Inscrire la catastrophe dans l’histoire. (Re)lectures de Leonardo Bruni et de Biondo Flavio - Laurent Baggioni (Laboratoire Italien)
The first half of the fifteenth century saw the emergence of a new historiography in Italy: written in a Latin language revived through the study of classical authors, it is described as "humanist". The article considers two major figures of this historiographical revival, Leonardo Bruni and Biondo Flavio, and focuses on the way in which the former’s Historiarum populi Florentini libri and the latter’s Historiarum ab inclinatione Romani imperii decades interweave ancient history and contemporary history. In both texts, the catastrophic collapse of the Roman Empire appears as a fundamental and indispensable component of the historical narrative. By examining the narrative and ideological aspects of this theme, the article conducts a comparative analysis of the two works and highlights the primarily moral function of the disaster, reflective of the continuing prophetic vocation of history.